PKM Guru Pembina Olimpiade Matematika Dan IPA SD Di Wilayah Gugus I Kecamatan Banawa Selatan Kabupaten Donggala - Pathuddin Pathuddin; Linawati Linawati (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
Partners of the Community Partnership Program (PKM) are the SD Teachers Working Group (KKG) Cluster I Region. Problems faced by partner groups: 1). The mastery of the teachers / KKG members on the material and discussion of math and science Olympiad questions is still low. 2) The elementary school teachers in the cluster I areas were generally D2 and S1 PGSD alumni, where at the time they were studying only basic mathematics and science material, which had a low level of abstraction. This causes teachers / KKG members in the region to often misunderstand the basic concepts of mathematics and science. 3). In addition, references that can be used as enrichment materials are also lacking, and 4). Available sources to ask questions about the mathematics and science Olympiad material are also lacking, because the South Banawa sub-district is located in the border area of ​​the provinces of Central Sulawesi and West Sulawesi. The goal of PKM is to improve the ability of elementary school teachers to solve math and science Olympiad questions, so that later they can guide students who will take part in the district, provincial and national level Olympiad. The expected output target in PKM activities is that at least 5 KKG members in the cluster I region can work on the 2019 city level Olympic questions, so that they can guide their students to qualify for the provincial level selection. After this activity is completed, the participants are expected to be able to pass on their knowledge to other fellow teachers. The book is the result of discussion of Olympic questions at the city and provincial levels, the work of the regional KKG members to be used as one of the future references. To achieve this target, the method used in this PKM activity is to provide training on material and discussion of mathematics and science Olympiad questions, basic concepts of mathematics and science which are important and support for following mathematics and science materials which require higher analysis. Provide assistance to ensure the material presented to partners can be implemented properly so that the results obtained can reach the target.